3D microstructure design of lithium-ion battery electrodes assisted by X-ray nano-computed tomography and modelling - Lu, Xuekun; Bertei, Antonio; Finegan, Donal P.; Tan, Chun; Daemi, Sohrab R.; Weaving, Julia S.; O’Regan, Kieran B.; Heenan, Thomas M. M.; Hinds, Gareth; Kendrick, Emma; Brett, Dan J. L.; Shearing, Paul R. (Nature communications, 2020)
Driving range and fast charge capability of electric vehicles are heavily dependent on the 3D microstructure of lithium-ion batteries (LiBs) and substantial fundamental research is required to optimise electrode design for specific operating conditions. Here we have developed a full microstructure-resolved 3D model using a novel X-ray nano-computed tomography (CT) dual-scan superimposition technique that captures features of the carbon-binder domain. This elucidates how LiB performance is markedly affected by microstructural heterogeneities, particularly under high rate conditions. The elongated shape and wide size distribution of the active particles not only affect the lithium-ion transport but also lead to a heterogeneous current distribution and non-uniform lithiation between particles and along the through-thickness direction. Building on these insights, we propose and compare potential graded-microstructure designs for next-generation battery electrodes. To guide manufacturing of electrode architectures, in-situ X-ray CT is shown to reliably reveal the porosity and tortuosity changes with incremental calendering steps. The 3D microstructure of the electrode predominantly determines the electrochemical performance of Li-ion batteries. Here, the authors show that the microstructural heterogeneities lead to non-uniform Li insertion and current distribution while graded-microstructures improve the performance.